An Unusual Case of Recurrent Pyocolpos Following Midtrimester Miscarriage Revealed as Obstructed Hemivagina with Ipsilateral Renal Agenesis (OHVIRA) Syndrome - Shamim Khandaker; Madhusudan Haldar; Shyamal Dasgupta; Shabana Munshi; Nabojibon Mondal; Sudhir Adhikari (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2014)
Obstructed hemivagina with ipsilateral renal agenesis (OHVIRA Syndrome) is a rare congenital anomaly. It mostly presents with severe dysmenorrhea and a palpable mass due to unilateral hematocolpos. Sometime it presents in unusual way with prolonged vaginal bleeding and profuse vaginal discharge. We report a case of an 18-year-old married female with OHVIRA syndrome presenting late with symptoms of recurrent pyocolpos following dilatation and evacuation for midtrimester miscarriage that was diagnosed on the basis of MRI and managed by vaginal septotomy.